(untitled) (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
This study aims to describe the Arabic language learning strategies implemented at Pesantren Darul Arqam Muhammadiyah Balassuka and to analyze their effectiveness in improving students’ language competence. This research employs a qualitative approach with a descriptive design in which data were obtained through observations, interviews, and documentation. The findings reveal that the pesantren applies various learning strategies, including classroom-based classical instruction, private talaqqi sessions, daily muhadatsah, vocabulary memorization, the establishment of a language area, and the use of audio-visual learning media. The disciplined pesantren environment and the integration of Arabic into students’ daily activities strengthen the internalization of the language. Moreover, the active role of teachers in guiding and monitoring learning progress serves as a supporting factor contributing to the effectiveness of these strategies. However, challenges were identified, such as uneven student motivation and limited technological learning facilities. Overall, the strategies implemented are considered effective in enhancing Arabic language skills among students, yet continuous innovation remains necessary to optimize learning outcomes.